Evaluation of the Gratitude Questionnaire in a Chinese Sample of Adults: Factorial Validity, Criterion-Related Validity, and Measurement Invariance Across Sex - Kong, Feng; You, Xuqun; Zhao, Jingjing (Frontiers in Psychology, 2017)
The Gratitude Questionnaire (GQ; McCullough et al. 2002) is one of the most widely used instruments to assess dispositional gratitude. The purpose of this study was to validate a Chinese version of the GQ by examining internal consistency, factor structure, convergent validity and measurement invariance across sex. A total of 1151 Chinese adults were recruited to complete the GQ, Positive Affect and Negative Affect Scales, and Satisfaction With Life Scale. Confirmatory factor analysis indicated that the original unidimensional model ﬁtted well, which is in accordance with the findings in Western populations. Furthermore, the GQ had satisfactory composite reliability and criterion-related validity with measures of life satisfaction and affective well-being. Evidence of configural, metric and scalar invariance across sex was obtained. Tests of the latent mean differences found females had higher latent mean scores than males. These ﬁndings suggest that the Chinese version of GQ is a reliable and valid tool for measuring dispositional gratitude and can generally be utilized across sex in the Chinese context.